2014
DOI: 10.1016/j.jns.2014.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone-dependent epigenetic suppression of herpes simplex virus-1 gene expression and viral replication in differentiated neuroendocrine cells

Abstract: A global HSV-1 gene repression occurs during latency in sensory neurons where most viral gene transcriptions are suppressed. The molecular mechanisms of gene silencing and how stress factors trigger the reactivation are not well understood. Thyroid hormones are known to be altered due to stress, and with its nuclear receptor impart transcriptional repression or activation depending upon the hormone level. Therefore we hypothesized that triiodothyronine (T3) treatment of infected differentiated neuron like cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(51 citation statements)
references
References 46 publications
3
48
0
Order By: Relevance
“…It was shown that Vero cells have very low TRβ1 expression [37]. The infection of Vero cells with A1 virus, the HSV-1 without TRβ1 transgene , did not increase the expression (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…It was shown that Vero cells have very low TRβ1 expression [37]. The infection of Vero cells with A1 virus, the HSV-1 without TRβ1 transgene , did not increase the expression (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…3C). In addition, infection of A1 did not show this regulatory consequence [37], indicating this T 3 -mediated replication increase resulted from the presence of TRβ1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, ChIP has shown that during productive herpes simplex virus 1 (HSV-1) infection, virus gene transcription is regulated, in part, by binding of virus (26) or host (27) proteins to specific DNA sequences within gene promoters or to protein components of the transcriptional apparatus (28). Importantly, ChIP analyses of HSV-1-infected neurons have shown that posttranslational modification of histone proteins is a critical factor that maintains the unique transcriptional pattern of virus genes during latency.…”
Section: Discussionmentioning
confidence: 99%